ST-segment Elevation Following Cardioversion of Atrial Fibrillation in the Emergency Department: Unmasked Myocardial Infarction due to Left Main Coronary Artery Plaque Rupture or Unspecific Finding?. Issue 4 (13th September 2016) - Prochnau, Dirk; Surber, Ralf; Hoyme, Matthias; Otto, Sylvia; Selle, Anna; Poerner, Tudor C.
Abstract: Atrial fibrillation (AF) is a frequent reason for emergency department visits. According to current guidelines either rate- or rhythm-control are acceptable therapeutic options in such situations. In this report, we present the complicated clinical course of a patient with AF and a rapid ventricular response. Because of paroxysmal AF, the patient was on chronic oral anticoagulation therapy with warfarin. Pharmacological treatment was ineffective to control ventricular rate, and immediate synchronized electrical cardioversion was performed. One hour later, the patient complained of chest pain in combination with marked ST-segment elevation in the anterior leads. Cardiac catheterization with optical coherence tomography disclosed plaque rupture in the left main coronary artery without other significant stenosis. Stent implantation was performed successfully. During the course of the hospital stay, the patient remained asymptomatic and the ST-segment elevations resolved. However, despite treatment with amiodarone it was not possible to keep the patient permanently in sinus rhythm. Therefore, a biventricular pacemaker was implanted and AV node ablation performed. RÉSUMÉ: La fibrillation auriculaire (FA) est un motif fréquent de consultation au service des urgences. Selon les lignes de conduite actuelles, le rétablissement ou de la fréquence cardiaque ou du rythme cardiaque sont des formes acceptables de traitement dans le contexte. Il sera question, dans le présent exposé, de l'évolution clinique, avec complications, d'un cas de FA accompagnée d'une réponse ventriculaire rapide. Comme le patient souffrait déjà de FA paroxystique, il était soumis à un traitement anticoagulant oral prolongé par la warfarine. Le traitement pharmacologique n'ayant pas permis de rétablir la fréquence ventriculaire, une cardioversion électrique synchronisée a été effectuée sans délai. Une heure plus tard, le patient a commencé à se plaindre de douleurs thoraciques, et une forte élévation du segment ST a été observée à l'électrocardiogramme, dans les dérivations antérieures. Les médecins ont alors procédé à un cathétérisme cardiaque avec tomographie par cohérence optique, qui a révélé la rupture d'une plaque dans le tronc coronaire gauche, sans autre signe important de sténose; l'examen a été suivi de la pose réussie d'une endoprothèse. Durant son séjour à l'hôpital, le patient est resté asymptomatique, et l'élévation du segment ST est disparue. Toutefois, malgré le traitement par l'amiodarone, le cœur ne s'est jamais maintenu en rythme sinusal d'une façon durable. Aussi l'arythmie a-t-elle justifié la pose d'un stimulateur cardiaque biventriculaire et l'ablation du nœud auriculo-ventriculaire.